Peran Sistem Informasi Manajemen dalam Pengelolaan Data Jamaah Umrah: Kajian Literatur Sistematis (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study conducts a systematic review of literature concerning the role of Management Information Systems (MIS) in managing Umrah pilgrim data across Indonesia. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, the study examined and synthesized 24 peer-reviewed articles published between 2019 and 2026, drawn from Google Scholar, SINTA, and nationally accredited journal portals. Findings indicate that MIS adoption has yielded notable improvements in operational efficiency, data reliability, service transparency, and the overall quality of managerial decision-making within Umrah travel organizations. Web-based MIS remains the predominant technological approach, offering integrated modules for pilgrim registration, document handling, financial tracking, and departure scheduling. At the national level, government-initiated platforms such as SISKOHAT and SISKOPATUH have demonstrated tangible contributions to the administration of Hajj and Umrah services. Nevertheless, persistent obstacles continue to hinder full-scale adoption, including inadequate digital infrastructure in certain regions, inconsistent internet connectivity, and gaps in human resource competencies for operating digital systems. The study argues that embracing MIS is no longer optional for Umrah travel operators; rather, it constitutes a strategic necessity. Future research is encouraged to investigate long-term implementation outcomes, cross-system comparisons, and data security considerations within the broader digital landscape of pilgrimage service management.